Evaluating correlates of healthy eating and dietary quality among older adults: a mixed methods approach to development and application of a new survey instrument - Biggins, Anna Marie (Kansas State University, 2022)
Background: Community-dwelling older adults face unique challenges related to nutrition and health, but little is known about their unique barriers and facilitators for healthy eating behaviors. This study sought to develop a new instrument to measure the capability, opportunity, and motivation for healthy eating behaviors (COM-HE) among community-dwelling older adults. It also aimed to assess the validity, reliability, and acceptability of the new instrument and to examine associations between the COM-HE instrument and self-reported dietary quality. Methods: A mixed methods approach was used to obtain qualitative and quantitative data. Participants were aged 65 years or older, community-dwelling, and English-speaking. Participants engaged in focus groups (n = 12) and pilot testing (n = 81) to evaluate the COM-HE instrument. The REAP-S questionnaire was utilized to examine correlations between the COM-HE instrument and self-reported dietary quality. Descriptive and inferential statistics were used to highlight potential relationships between study variables. Results: The COM-HE instrument achieved acceptable internal validity (Cronbach’s alpha = 0.847–0.986), displayed varying levels of unidimensionality based on multiple principal component analyses (total variance explained by three components = 86.72%), and was correlated with self-reported dietary quality scores (r = .409, adjusted R² = .099, p < .05). Preliminary data suggest that the scale was acceptable in terms of readability and understanding among a convenience sample of well-educated older adults. Conclusion: The new COM-HE instrument was acceptable, reliable, and valid among a homogenous sample of adults over 65 years of age. These results suggest a need for additional development, evaluation, and refinement of the instrument in more diverse groups of older adults.
Keywords: Healthy eating; Older adults; COM-B model; Mixed methods; Survey development; Dietary quality